Associations Between Environmental Conditions and Executive Cognitive Functioning and Behavior During Late Childhood: A Pilot Study - Fishbein, Diana H.; Michael, Larry; Guthrie, Charles; Carr, Christine; Raymer, James (Frontiers in Psychology, 2019)
Numerous studies have established the influence of detrimental home conditions on child cognition and behavior; however, fewer have assessed these outcomes in the context of relatively “normal” range of home environmental conditions. Given the exquisite sensitivity to the environment of the neural substrates that undergird executive functioning (EF) and behavioral self-regulation in children, it is possible that a range of conditions within the home, even in the absence of maltreatment or economic deprivation, may impact these outcomes. The purpose of the present exploratory investigation was to further define the relationship between features of the home environment using the HOME inventory (a structured interview and observation of parent and child) and several dimensions of child EF and behavioral problems. In addition, this study sought to elucidate potentially differential associations between home and parent-reported neighborhood conditions—a hypothetically less direct influence on cognition in this age group—and level of child functioning. A battery of EF performance tasks and a widely-used checklist of behavioral problems were administered to 66 children, 8-11 years old from a lower middle income, working class sample. Results showed significant relationships between the home environment and several dimensions of EF and behavioral problems. In contrast, neighborhood conferred additional effects only on rule-breaking and aggression, not cognition, which is consistent with evidence that externalizing behavior in this age group becomes increasingly oriented toward outside influences. These findings warrant follow-up studies to establish causality. A broader program of research designed to delve further into the relationship between nuanced influences from the home and child cognition and behavior has implications for parenting strategies that foster healthy development. Neighborhood contexts should also be considered during early and mid-adolescent years based on existing studies and findings reported herein suggesting that this period of newfound autonomy and the heightened significance of peer relationships may influence externalizing behaviors, with implications for protective courses of action.